Peran Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Kinerja Tenaga Pendidik - Rohimah Aprilia Irawati; Sitti Zuhrotul Fadilah; Ayu Umi Salamah (Universitas Maritim AMNI Semarang, 2025)
The purpose of this article is to understand the importance of transformational leadership in improving teaching staff productivity. This research uses a systematic approach to literature review by analyzing individual articles from national and international journals. The results of the literature review show that the school's transformational leadership in improving teaching staff performance includes: 1) creating a collaborative and inspiring environment, 2) providing intellectual and innovative stimulation, 3) involving students, and 4) providing constructive feedback.